Race/Ethnicity Differences in COVID-19 Vaccine Uptake Among Nurses. (March 2022) - Choi, Kristen; Rondinelli, June; Cuenca, Emma; Lewin, Bruno; Chang, John; Luo, Yi X.; Bronstein, David; Bruxvoort, Katia
Introduction: There is evidence for relatively lower COVID-19 vaccine uptake among people of color in the United States. The purpose of this study was to investigate associations between race/ethnicity and COVID-19 vaccine uptake among nurses. Methods: Nurses in Southern California ( N = 1183) completed a one-time, web-based survey to assess COVID-19 vaccine perceptions and uptake. Results: In all, 82.8% of respondents ( N = 979) received at least one COVID-19 vaccine dose. Identifying as East Asian was associated with 14% higher odds of COVID-19 vaccine uptake relative to identifying as White (odds ratio [OR] = 1.14/95% confidence interval [CI] = [1.06, 1.24]); identifying as Filipino was associated with 14% higher odds of uptake (OR = 1.14/95% CI = [1.08, 1.20]); and identifying as Hispanic/Latinx was associated with 6% higher odds of uptake (OR = 1.06/95% CI = [1.00, 1.12]). Discussion: Although nurses and people of color have been identified as groups with low levels of COVID-19 vaccine uptake, this study found that nurses of color received the vaccine at higher levels than their White counterparts.